2012
DOI: 10.1021/ja303356z
|View full text |Cite
|
Sign up to set email alerts
|

Making Insoluble Polymer Networks Malleable via Olefin Metathesis

Abstract: Covalently cross-linked polymers have many technological applications for their excellent properties, but they suffer from the lack of processability and adaptive properties. We report a simple, efficient method of generating adaptive cross-linked polymers via olefin metathesis. By introducing a very low level of the Grubbs' second-generation Ru metathesis catalyst, a chemically cross-linked polybutadiene network becomes malleable at room temperature while retaining its insolubility. The stress relaxation capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
446
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 517 publications
(448 citation statements)
references
References 32 publications
2
446
0
Order By: Relevance
“…32,36,37 We chose to copolymerize 3 with CO to control the amide mole fraction in ACON (Scheme 1b). Following our reported protocol, 38 the ACON polymer was cross-linked by radical reaction and G2 was incorporated by swelling ( Table 1. The molecular weights for the hydrogen bonding and control polymers are very close.…”
Section: Resultsmentioning
confidence: 99%
“…32,36,37 We chose to copolymerize 3 with CO to control the amide mole fraction in ACON (Scheme 1b). Following our reported protocol, 38 the ACON polymer was cross-linked by radical reaction and G2 was incorporated by swelling ( Table 1. The molecular weights for the hydrogen bonding and control polymers are very close.…”
Section: Resultsmentioning
confidence: 99%
“…8). 40,41 This catalyst was used because of its superior stability towards air and moisture and its good functional group compatibility, as compared to more classical metathesis catalysts. 42 Networks were first prepared through free radical cross-linking of polybutadiene initiated by benzoyl peroxide.…”
Section: Vitrimer-like Materialsmentioning
confidence: 99%
“…Currently, as recently reviewed by our group9, only a limited number of associative exchange chemistries101112131415161718192021222324 have been explored in the context of vitrimers, and one of the main challenges is the precise control of the exchange kinetics. Although Leibler and co-workers demonstrated that epoxy-based transesterification vitrimers can be controlled by changing catalysts8, the exchange reaction remains slow and high catalyst loadings and temperatures are required to enable processing in a reasonable timeframe678.…”
mentioning
confidence: 99%